ANALYSIS OF EARLY AND LATE OUTCOMES OF TAPVC REPAIRS– A SINGLE SURGEON’S PERSPECTIVE OBSERVATIONAL STUDY - Dr. Murtaza SM; Dr. Anurag Goyal; Amitabh satsangi; Dr. Devagourou Velayoudam (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Total anomalous pulmonary venous connection (TAPVC) is a congenital heart defect. Without surgical correction, it has a high mortality rate. Owing to the improved perioperative care and surgical techniques, the overall results have also improved. Our study assesses the early and late outcomes of TAPVC repairs done over last 10 years under a single surgeon. Methods: Eighty-eight patients who were surgically treated for TAPVC over last 10 years from 01 June 2009 to 31 May 2019 by a single surgeon formed the basis of this retrospective observational study. The information regarding patient demographic details, pre-operative evaluation, surgical procedure, post-operative course and follow up after discharge was retrieved by searching operation theater registries, medical record sections and finally by patient follow up in outpatient department/telephonic follow up. Results: Mean age and weight at surgery were 10.82 months and 5.27 kg respectively. Out of 88, 64 (72.7%) were male patients and 24 (27.3%) were females. 25% of the participants had Age ≤1 Month. The TAPVC anatomy was supra-cardiac in 41 (46.6%) cases, cardiac in 24 (27.3%), infra-cardiac in 14 (15.9%) and mixed in 9 (10.2%). Of the 88 TAPVC patients, 33 (37.5%) were obstructed at the time of operation. Twenty-nine (33%) patients had to be taken up for emergency TAPVC repair. The vertical vein was left open in 34 cases (38.6%). Mean duration of mechanical ventilation was 4.18 days (+/-2.17 SD). Mean ICU stay was 8.01 days (+/-3.63 SD). Mean hospital stay was 17.8 days (+/-10.47 SD). Eleven (12.5%) patients died in the early post-operative period. There were 3 late deaths, 2 of which occurred in infra-cardiac TAPVC patients, while the third was of mixed TAPVC type. Conclusions: Early mortality was found to be 12.5%, while late mortality was 3.9%. All the patients included in our study have been operated by a single surgeon, thus eliminating bias. Our study emphasizes the fact that the overall outcome of TAPVC repair has improved compared to previous similar studies, mostly as a result of advancement of management strategies, both medical and surgical.